Endovascular interventions : a case-based approach - Dieter, Jr., Raymond A.; Dieter, III, Raymond A.; Dieter, Robert S. (Springer New York, 2014)
Due to significant advances in minimally invasive techniques, the endovascular approach is being increasingly used in the treatment of vascular diseases.  Endovascular interventions avoid  the trauma of conventional surgery, particularly for patients who are at high risk due to age or comorbidity.  Endovascular Interventions: A Case-Based Approach presents the current methodology underlying the endovascular treatment of peripheral arterial and venous disorders.  Using a case-based approach, it presents readers with a range of complexities and complications encountered in daily practice, together with tips and tricks for overcoming them.  The editors, Robert Dieter, Raymond Dieter, Jr., Raymond Dieter, III, and Aravinda Nanjundappa, are recognized for their work in interventional cardiology and cardiothoracic and vascular surgery and bring a unique perspective to the use of these approaches.  The chapters are written by leading international authorities in endovascular treatment of arterial, venous, and lymphatic vessels and discuss the conditions for which these interventions are appropriate, including intracranial strokes, restenotic lesions, subclavian artery stenosis, upper and lower extremity artery disease, ascending aortic pseudoaneurysm, abdominal aortic aneurysm, complications of intra-aortic balloon pumps, vasculitis, and iatrogenic aortic dissection.  This book is a practical guide and valuable resource for practicing vascular specialists, interventional cardiologists, interventional radiologists, vascular surgeons, and cardiothoracic surgeons. Foreword by Denton A. Cooley, MD, President Emeritus and Surgeon-in-Chief, Texas Heart Institute.